2013
DOI: 10.21608/avmj.2013.171497
|View full text |Cite
|
Sign up to set email alerts
|

Otitis Externa and Otitis Media in Cats in Assiut: A Retrospective Study of Presenting Signs, Causes, Diagnosis and Treatment

Abstract: In this study, records of cases admitted to the Small Animal Clinic (SAC), Veterinary Teaching Hospital (VTH) at Assiut University, between years 2007-2011 for investigation of signs of otitis were reviewed and data analyzed. Points of analysis comprised presenting clinical signs, results of otoscopic examination, identification of cause of otitis and outcome of treatment of each cat. Treatments used for these cases were either ivermectin injection or topical treatment with antimicrobial/anti-inflammatory ear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…Ear mange in cats was considered a problem in Egypt. In our study, the overall prevalence of mange mite is 70%, which agrees with another study that reported more than 59% in Egypt between 2007 and 2011 (Waly and Khalaf 2013). Epidemiological findings revealed that cats less than one-year-old were more susceptible to the disease than old ones.…”
Section: Discussionsupporting
confidence: 91%
“…Ear mange in cats was considered a problem in Egypt. In our study, the overall prevalence of mange mite is 70%, which agrees with another study that reported more than 59% in Egypt between 2007 and 2011 (Waly and Khalaf 2013). Epidemiological findings revealed that cats less than one-year-old were more susceptible to the disease than old ones.…”
Section: Discussionsupporting
confidence: 91%